Предмет: Алгебра,
автор: Аноним
Решите уравнение
(x−3)(x−4)(x−5)=(x−2)(x−3)(x−5).
Ответы
Автор ответа:
0
(x−3)(x−4)(x−5)=(x−2)(x−3)(x−5)
(x−3)(x−4)(x−5) - (x−2)(x−3)(x−5) = 0
(x−3)(x−5) * ((x−4) - (x−2)) = 0
(x−3)(x−5) * (x−4 - x+2) = 0
- 2 * (x−3)(x−5) = 0 // : (-2)
(x−3)(x−5) = 0
x1 = 3
x2 = 5
(x−3)(x−4)(x−5) - (x−2)(x−3)(x−5) = 0
(x−3)(x−5) * ((x−4) - (x−2)) = 0
(x−3)(x−5) * (x−4 - x+2) = 0
- 2 * (x−3)(x−5) = 0 // : (-2)
(x−3)(x−5) = 0
x1 = 3
x2 = 5
Похожие вопросы
Предмет: Русский язык,
автор: umbetovadilyara
Предмет: История,
автор: Аноним
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: DaMIXArK
Предмет: Математика,
автор: Ырррчплпрлл